1998
DOI: 10.1159/000025887
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Upregulates Aminopeptidase N and 5′–Nucleotidase in Human Glomerular Mesangial Cells

Abstract: Because epidermal growth factor (EGF) is likely to be released in the glomeruli during glomerular injury and mesangial cells possess specific receptors for EGF, we thought it to be of interest to examine whether this growth factor could influence the expression of ectoenzymes in cultured human mesangial cells. EGF stimulated 5′–nucleotidase and aminopeptidase N activities in intact human mesangial cells in a time– (24–72 h) and dose–dependent (0.1–50 ng·ml–1) manner. Maximum stimulation represented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Fetal calf serum contains some growth factors which could influence aminopeptidase N expression. Previously, we identified in serum epidermal growth factor (EGF) and showed that aminopeptidase N is upregulated upon treatment of human mesangial cells with nanomolar concentrations of EGF [11]. Dermal fibroblast aminopeptidase N was unaffected following treatment with cAMP in the concentration range from 10 to 500 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal calf serum contains some growth factors which could influence aminopeptidase N expression. Previously, we identified in serum epidermal growth factor (EGF) and showed that aminopeptidase N is upregulated upon treatment of human mesangial cells with nanomolar concentrations of EGF [11]. Dermal fibroblast aminopeptidase N was unaffected following treatment with cAMP in the concentration range from 10 to 500 mM.…”
Section: Discussionmentioning
confidence: 99%